Magnetic template-assisted construction of 2D PCN/TiO₂ heterostructures for efficient photocatalytic hydrogen generation - Sun, Jiajun (2023)
Two-dimensional (2D) heterostructures with large interfacial area have great potentials as highly efficient photocatalysts. In this work, we report fabrication of 2D heterostructures of TiO2 and polymeric carbon nitride (PCN) by using Fe3O4 microplates as the template and sequentially growing very thin layer of PCN and TiO2 on the microplate surface followed by removal of Fe3O4. The magnetic Fe3O4 templates provide unique advantages for convenient magnetic separation of the grown 2D heterostructures from other by-products in solution. The obtained 2D PCN/TiO2 heterostructures with an average total thickness of 25 nm showed excellent photocatalytic hydrogen generation rate (11.1 μmol h−1), which was much higher than that of individual PCN and TiO2 nanosheets as well as the bulk PCN/TiO2 heterojunctions. The high photocatalytic activities could be attributed to the large contacting area between PCN and TiO2 that enable effective separation and transport of photogenerated electrons and holes through the PCN/TiO2 interfaces. Our studies provide a new and general approach to fabricate 2D heterostructures for high efficiency photocatalysis.